(untitled) (Orfeu, 2025)
Mônica Giardini stands out as a conductor and educator committed to the recognition and development of symphonic bands in Brazil. Her musical journey began in childhood, influenced by family and school experiences. She believes that the symphonic band represents the orchestra of the 21st century, providing a space for innovation and musical excellence. Her academic background includes a master’s and Ph.D from the USP, yet she emphasises that her expertise was truly shaped through practical experience and international studies. Throughout her career, she has faced structural challenges and institutional biases but has consistently prioritized artistic and pedagogical quality. A strong advocate for social inclusion and music education, she considers it essential for conductors to have instrumental proficiency, stylistic knowledge, and sensitivity to lead diverse ensembles effectively. Her leadership of the São Paulo State Youth Symphonic Band reflects her mission: to transform the band into a space of excellence and musical innovation.